2022
DOI: 10.1016/j.jsxm.2022.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Analysis of a New Oral Testosterone Undecanoate (TU) Formulation in Hypogonadal Men: Efficacy, Impact on Psychosexual Function, and Safety

Abstract: Background Long-term data evaluating the efficacy and safety of oral testosterone undecanoate (oral TU; JATENZO) in adult hypogonadal men provides important information for healthcare professionals who prescribe testosterone replacement therapy (TRT). Aim To determine the efficacy and safety of long-term oral TU therapy, including its impact on total testosterone (T) levels and psychosexual functioning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 27 publications
0
0
1
Order By: Relevance
“…Here liver parameters among KS receiving TRT were within normative ranges. Studies in hypogonadal men have also demonstrated an improvement in liver function after two years of oral testosterone or when increasing the level of testosterone [24,25]. However, the present data did show a trend towards improvement in liver function in T-KS males indicating that TRT may improve liver function in males with KS.…”
Section: Discussioncontrasting
confidence: 82%
“…Here liver parameters among KS receiving TRT were within normative ranges. Studies in hypogonadal men have also demonstrated an improvement in liver function after two years of oral testosterone or when increasing the level of testosterone [24,25]. However, the present data did show a trend towards improvement in liver function in T-KS males indicating that TRT may improve liver function in males with KS.…”
Section: Discussioncontrasting
confidence: 82%